2015
DOI: 10.1093/pm/pnv074
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Pain Catastrophizing and Endogenous Pain Modulatory Processes in Adults with Chronic Low Back Pain

Abstract: This study suggests that endogenous pain modulatory processes are altered for cLBP patients, particularly TS of mechanical and heat stimuli. Pain catastrophizing and TS of mechanical pain may have important clinical relevance for cLBP, given associations with clinical pain and disability; however, future research is needed to replicate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 64 publications
6
39
1
5
Order By: Relevance
“…Ten consecutive stimuli were applied starting at a baseline temperature of 40°C and increasing within 8°C/s to 48°C, and returning to baseline at the same rate. The interstimulus interval was set at 2.5 seconds, adapted from a protocol by Owens et al …”
Section: Methodsmentioning
confidence: 99%
“…Ten consecutive stimuli were applied starting at a baseline temperature of 40°C and increasing within 8°C/s to 48°C, and returning to baseline at the same rate. The interstimulus interval was set at 2.5 seconds, adapted from a protocol by Owens et al …”
Section: Methodsmentioning
confidence: 99%
“…One of the first studies on impaired descending pain modulation in chronic LBP was published in 1992 (Peters et al, 1992), and later other studies have followed with the same result (Owens et al, 2016). Evidence has been provided that endogenous modulation is also impaired in acute LBP (Mlekusch et al, 2016) raising the question for how long the LBP should be present in order to have an impact on CPM.…”
Section: Descending Pain Controlmentioning
confidence: 96%
“…Remote testing of TSP has previously been shown to be altered in acute LBP patients 61 , and has been associated with higher pain intensity, increased disability and wider pain distribution in chronic LBP patients 11,49,66 . Hence, lack of facilitated TSP in the present study might suggest exercise-induced-LBP does not produce sufficient pain intensity, duration or distribution to No specific changes in ramped-CPM effects were observed, suggesting that descending inhibitory function remained intact despite LBP presence.…”
Section: Temporal Summation During Exercise-induced-lbpmentioning
confidence: 99%
“…For instance, TSP and CPM, assessed pre-operatively in painfree patients undergoing thoracotomy, demonstrated predictive value in determining postoperative pain intensity 70,75 . TSP and CPM magnitude in people with pain conditions can also relate to the intensity of pain experienced 5,49,65 , suggesting fluctuations in TSP and CPM may be consequential to pain 2,15 . In line with this suggestion, clinical studies have demonstrated improvements in CPM and pain sensitivity following replacement of painful osteoarthritic joints 18,30 , and experimental studies have shown impaired CPM following painful saline injection 2 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%